2013
DOI: 10.1371/journal.ppat.1003720
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormone Signaling Is Essential to Regulate Innate Immune Cells and Fight Bacterial Infection in Drosophila

Abstract: Coupling immunity and development is essential to ensure survival despite changing internal conditions in the organism. Drosophila metamorphosis represents a striking example of drastic and systemic physiological changes that need to be integrated with the innate immune system. However, nothing is known about the mechanisms that coordinate development and immune cell activity in the transition from larva to adult. Here, we reveal that regulation of macrophage-like cells (hemocytes) by the steroid hormone ecdys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 67 publications
3
128
0
Order By: Relevance
“…Several previous studies suggested that 20E could promote both cellular and humoral innate immunity, and this enhancement requires EcR in Drosophila (13)(14)(15)20). However, knowledge about the effects of 20E on immune response is very limited in lepidopteran insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies suggested that 20E could promote both cellular and humoral innate immunity, and this enhancement requires EcR in Drosophila (13)(14)(15)20). However, knowledge about the effects of 20E on immune response is very limited in lepidopteran insects.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of the prophenoloxidases could be induced in the Anopheles gambiae cell line 4a-3B (16). Injection with 20E increases the phagocytic activity of Drosophila plasmatocytes (17), and 20E signaling also enhances hemocyte motility, encapsulation, and nodulation (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…In addition, it is needed for the optimal phagocytic activity of hemocytes in response to bacteria (95). Ecdysone also was reported to regulate the activity of the Imd pathway in adult flies via its target genes, whose products are needed for PGRP-LC expression.…”
Section: Regulation Of the Imd Signaling Pathwaymentioning
confidence: 99%
“…Humoral and cellular immune responses are usually studied in both larvae and adults. Since the maturation of immune responsiveness is strongly dependent on ecdysone [9,10], immune pathways in the adult stage are less affected by developmental timing. It should be noted that AntiMicrobial Peptides (AMPs) (and many immune genes) show very high levels of inducibility (equivalent to heat-shock genes).…”
Section: Introductionmentioning
confidence: 99%